THE CLINICO-LABORATORY CHARACTERISTIC OF MIXED VIRAL INTESTINAL INFECTIONS IN CHILDREN IN BAKU CITY - Lala Islakhovna Rustamova; Zemfira Mekhdiyevna Kuliyeva; Fatma Vagifovna Qilindjova; Mekhriban Musayevna Isayeva; Rena Mamedovna Akhundova (Siberian Journal of Life Sciences and Agriculture, 2020)
The aim of investigation was to study of epidemiological and clinical characteristics of mixed viral intestinal infections in children. The etiological diajnostic of acute intestinal infection of viral origin have been carried out by serological method (immunochromatographyc method). It was determined that the mixed viral intestinal infections as primary infected mainly have been registrated in children of first two years of life. In the age structure of viral-viral intestinal infections the rotaviral-adenoviral association have been oftenly appeared than rotaviral-astroviral association. The our investigations show that in mixed viral intestinal infections the most clinical form is gastroenteritis.